2019
DOI: 10.1159/000501790
|View full text |Cite
|
Sign up to set email alerts
|

DNA Ploidy Analysis and Cell Block Immunohistochemistry in the Diagnosis of Malignant Effusions

Abstract: Background: Effusion cytology is a major diagnostic tool in medicine and has both therapeutic and prognostic implications. One of the dilemmas encountered is the differentiation between atypical cells and reactive mesothelial cells. The use of ancillary tools can reduce this grey zone and help to achieve a definitive diagnosis. Objectives: The main objective of this study was to evaluate the role of flow cytometry (FCM) and cell block with immunohistochemistry (IHC), along with the clinicoradiological investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The reasons are considered to include diploid tumors or the presence of chromosome replication and chromosome deletion in some tumors, which lead to the masking of abnormal DNA results, which indicated that the ECS + CB analyses gave false negative results and confirmed the accuracy of the cellular DNA–ICM results. There was no statistical difference between the three methods, similar to the results found by Puri 29 …”
Section: Discussionsupporting
confidence: 88%
“…The reasons are considered to include diploid tumors or the presence of chromosome replication and chromosome deletion in some tumors, which lead to the masking of abnormal DNA results, which indicated that the ECS + CB analyses gave false negative results and confirmed the accuracy of the cellular DNA–ICM results. There was no statistical difference between the three methods, similar to the results found by Puri 29 …”
Section: Discussionsupporting
confidence: 88%
“…ICC has been shown to have superior staining results in cell blocks compared to conventional smears and LBC specimens. 9,[13][14][15] In this study, we prepared cell blocks from cells pretreated with an LBC fixative solution and cell blocks from LBC residual specimens. Our preliminary experiments showed that the immunostaining of cells treated with LBC fixative was lower than that of cells fixed with 10% NBF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, morphological approaches are limited, and ICC, FISH, and nucleic acid sequence analyses using DNA and RNA extraction are useful. ICC has been shown to have superior staining results in cell blocks compared to conventional smears and LBC specimens 9,13–15 . In this study, we prepared cell blocks from cells pretreated with an LBC fixative solution and cell blocks from LBC residual specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is difficult to diagnose some atypical cells only with cytological specimens. With the help of some auxiliary tools, this gray area can be reduced, which is helpful to achieve a clear diagnosis ( 7 ). Previous studies have shown that some laboratory indicators, such as various tumor markers, vascular endothelial growth factor, and serum BNP ( 8 10 ), have certain value in the differential diagnosis of benign and malignant PE.…”
Section: Introductionmentioning
confidence: 99%